Տահա Հուսեյնի «Օրերը» ինքնակենսագրական երկը և եգիպտական գրականությունը - Կարապետյան, Նաիրա («Զանգակ - 97»)
This article deals with the autobiographic work ' T h e Days" of Taha Husayn - one of the greatest novelists of Egypt at the beginning of the X X Century. The author is blind and the hero of the chronology is also blind. The chronology consists of two parts and the first part is the biography of young Taha Husayn. In the article we tried to give the brief view of his biography and the political Situation of Egypt since 1919 tili 1922-23,when Egypt received Independence and the First Constitution.
Keywords: Բանասիրություն